High prevalence of spotted fever group rickettsiae in ticks collected from yaks (Bos grunniens) in Shiqu county, eastern Tibetan Plateau, China - Baoshan Lin; Baoshan Lin; Yin Ta; Lili Hao (Frontiers in Microbiology, 2022)
Tick-borne diseases have become a global health concern in recent decades. Spotted fever group (SFG) rickettsiae have been recognized as important pathogens of human tick-borne diseases worldwide. In this study, Dermacentor everestianus (n = 646) and Haemaphysalis qinghaiensis (n = 172) ticks were collected from yaks (Bos grunniens) in Shiqu county, eastern Tibetan Plateau, China. SFG rickettsiae were identified and characterized in these ticks. A total of 49.9% (408/818) ticks were infected by Rickettsia spp. with infection rates of 58.1% (100/172) and 46.7% (308/646) detected in H. qinghaiensis and D. everestianus ticks, respectively. Furthermore, 95% of Rickettsia spp. were Rickettsia raoultii-like bacteria, and 5% were related to Candidatus Rickettsia longicornii. To the best of our knowledge, this is the first time that SFG rickettsiae infections were firstly reported in Shiqu county for these tick species. Our results indicated that H. qinghaiensis and D. everestianus ticks from Shiqu county became highly infected with a R. raoultii-like bacteria during their feeding process. This observation is alarming because of the zoonotic potentiality of these species. Overall, the present study detected a widespread of R. raoultii-like bacteria in ticks that are considered a serious threat to domestic animals and humans in Shiqu county. The prevalence of R. raoultii-like bacteria in human and wildlife hosts should be further investigated in the future.